2018
DOI: 10.25100/socolen.v44i1.6758
|View full text |Cite
|
Sign up to set email alerts
|

New records of Ephemeroptera from the Colombian Orinoco river basin of the Meta department

Abstract: Se corrigen las palabras clave así: Palabras clave: Distribución, Andina-Orinoco, pie de monte, taxonomía.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…En la región Neotropical existen 16 familias, con cerca de 130 géneros y 820 especies, número que se ha incrementado en los últimos 10 años (Domínguez & Dos Santos, 2013, Cardoso et al, 2015Hamada et al, 2018, Domínguez et al, 2019. En Colombia, son importantes contribuciones al conocimiento de la riqueza y distribución de este grupo los trabajos de Días et al (2009), Gutiérrez & Reinoso (2010), Salinas et al (2012), Gutiérrez & Días (2015), Rúa et al (2015), Barrios-Núñez & Granados-Martínez (2016), Salinas-Jiménez et al (2017), Granados-Martínez et al (2018, Chaux-Rojas (2020), entre otros. En el país se conocen nueve familias, 42 géneros y aproximadamente 86 especies (Domínguez et al, 2006;Días et al, 2009;García et al, 2013;Hoyos et al, 2014;Molineri, 2014;Gutiérrez & Llano, 2015;Zúñiga & Torres-Zambrano, 2015;Rozo & Salinas, 2016;Vinasco-Mondragón & Zúñiga, 2016).…”
Section: Introductionunclassified
“…En la región Neotropical existen 16 familias, con cerca de 130 géneros y 820 especies, número que se ha incrementado en los últimos 10 años (Domínguez & Dos Santos, 2013, Cardoso et al, 2015Hamada et al, 2018, Domínguez et al, 2019. En Colombia, son importantes contribuciones al conocimiento de la riqueza y distribución de este grupo los trabajos de Días et al (2009), Gutiérrez & Reinoso (2010), Salinas et al (2012), Gutiérrez & Días (2015), Rúa et al (2015), Barrios-Núñez & Granados-Martínez (2016), Salinas-Jiménez et al (2017), Granados-Martínez et al (2018, Chaux-Rojas (2020), entre otros. En el país se conocen nueve familias, 42 géneros y aproximadamente 86 especies (Domínguez et al, 2006;Días et al, 2009;García et al, 2013;Hoyos et al, 2014;Molineri, 2014;Gutiérrez & Llano, 2015;Zúñiga & Torres-Zambrano, 2015;Rozo & Salinas, 2016;Vinasco-Mondragón & Zúñiga, 2016).…”
Section: Introductionunclassified
“…Over 702 species have been reported in South America (Salles, et al, 2021) and roughly 123 are found in Colombia (Salinas-Jiménez, et al, 2017;Granados-Martínez, et al, 2018;Marulanda-López, et al, 2020;Marín-Eslava, et al, 2021;Dias, et al, 2021) with the families Leptophlebiidae, Leptohyphidae, and Baetidae as the more representative ones (more than the 65% of the species) (Salinas-Jiménez, et al, 2012, 2017. However, uncommon families remain poorly known in terms of geographical distribution, especially in the Northern region of South America.…”
Section: Introductionmentioning
confidence: 99%